MULTILATERAL GENERATING FUNCTIONS FOR THE MULTIPLE LAGUERRE AND MULTIPLE HERMITE POLYNOMIALS - Ozarslan, M. Ali; Ozergin, Emine; Kaanoglu, Cem (Eudoxus Press, Llc, 2010)
The main object of this paper is to derive several substantially more general families of bilinear, bilateral, and mixed multilateral finite-series relationships and generating functions for the multiple Laguerre and multiple Hermite polynomials. Some applications of the above statements are also given.
Keywords: Rodrigues formula; Generating function; Multiple Laguerre polynomials; Multiple Hermite polynomials; Finite-series relationship